“Efecto de la aplicación de biol de forma edáfica y foliar con dos concentraciones en el cultivo de fréjol (Phaselous vulgaris L.)”. - Morales Garcia, Antonia Alejandra (2023)
The present research was carried out at the Catalina farm in Cuatro Mangas precinct in Buena Fe canton. The purpose of this research was to analyze the effect of the application of biol in edaphic and foliar forms with two concentrations on the bean crop. The experiment was in a randomized block design with a factorial arrangement. Factor A was the way of applying biol (foliar and edaphic), and factor B was the dose (10 and 20 %), with 5 repetitions. The variables evaluated in this study were plant height, stem diameter, number of pods/plants, number of grains/pods, the weight of 100 grains, and yield kg/ha. The results were statistically processed in an analysis of variance and the comparison of means by Tukey multiple range test at 95 % probability. The statistical analysis showed no statistical difference in the factor ways of applying biol on the variables of growth and yield of the bean crop. However, the simple factor B (dose) differed statistically on the production and growth indicators of the bean plants, with the 10% dose being found to have the best plant height, stem diameter, and yield. In addition, the results reflected effects in the interaction of factors, finding that the application of foliar biol at a concentration of 10 % significantly increases the proliferation of pods (6.20) and the number of grains pods (6.21), which allows the best yield to be obtained with 218.50 kg/ha. Therefore, this treatment achieves the highest profitability with a B/C ratio of 2.10.